Integration of maize between rice and wheat with soil and nutrient management to improve productivity of rice-wheat cropping system in Bangladesh (Bangladesh Journal of Agricultural Research, 2019)
The necessity of more food production from limited land enforced cropping intensification over-exploring the natural resources in Bangladesh. This field experiment was initiated to achieve improve and sustainable productivity of an intensive wheat-maize-rice cropping system with improved management of natural resources. Four levels of nutrient managements were tested under four soil management treatments starting with wheat crop sown in November 2009 and ending with the harvest of 8th wheat crop in the system during March 2017. Yield and yield contributing characters of component crops and soil properties were studied following standard methods. Soil management treatment of rice straw mulch application in reduced till-bed or well-till flat soil upon wheat sowing was equally effective in conserving soil moisture, enhancing wheat root development, reducing weed growth and thereby positively influenced spikes/m2 and finally wheat yield. Similarly, wheat straw mulch application contributed to ears/m2 and grain yield of maize. Nutrient levels of recommended fertilizers plus 5.0 t/ha cowdung resulted in yield improvement of wheat and maize throughout the years. However, neither nutrient management nor soil management alone but the combination of recommended fertilizers with 5 t/ha cowdung couple with rice straw mulching in wheat and wheat straw mulching in maize resulted in maximum wheat and maize yield over the years. Rice yield was similar for different treatment combinations until the 4th cropping cycle and thereafter rice yield was also improved by the residual effect of straw mulches. Crop residue mulching along with addition of organic and inorganic fertilizers was found to be a promising soil management technology for achieving sustainable increased productivity of wheat-maize-rice system.Bangladesh J. Agril. Res. 44(2): 203-221, June 2019